Assessment of yield loss in cauliflower seed crop due to Alternaria blight - and KARUNA VISHUNAVAT*, LAKSHMAN PRASAD (Indian Phytopathology, 2006)
Alternaria blight caused by Alternaria brassicae (Berk.) Sacc. and A. brassicicola (Schw.) Wilts is responsible for poor seed quality, and yield losses in seed crop of Cauliflower (Brassica oleracea L. var. botrytis subvar. cauliflora). Yield loss due to the blight disease was studied in four cultivars viz., Pant Gobhi (PG) 2, PG 3, PG 4 (early maturing cultivars) and Pant-Subhra (a mid maturing cultivar). Highest seed yield losses (55.93) were found in mid maturing variety Pant Shubhra, inspite of being a variety giving highest curd productivity. Variety Pant Gobhi 4 gave highest seed yield (46.13) amongst the early maturing cultivars. The curd area infection is found directly proportional to seed yield losses in all the cultivars. The maximum loss (49.97%) in seed test weight was in cultivar PG2 at all the degree of pod area infection while minimum loss (9.69%) in seed test weight was found in Pant Subhra.